2012
DOI: 10.1111/j.1532-5415.2012.04239.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Depressive and Anxiety Disorders and Adherence to Antihypertensive Medication in Community‐Living Elderly Adults

Abstract: Adherence to antihypertensive medication was significantly associated with depression and anxiety disorders in men but not women. The treatment of depression and anxiety disorders in individuals with hypertension may be helpful in improving medication adherence rates and healthcare outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 29 publications
(44 reference statements)
7
51
5
1
Order By: Relevance
“…Adherence to therapy seems to have an association with depression and anxiety disorders in men (but not in women), offering the opportunity for treatment of the disorders to improve outcomes [130]. Even mild anxiety and depression increase the risk of nonadherence [131].…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to therapy seems to have an association with depression and anxiety disorders in men (but not in women), offering the opportunity for treatment of the disorders to improve outcomes [130]. Even mild anxiety and depression increase the risk of nonadherence [131].…”
Section: Depressionmentioning
confidence: 99%
“…Association between depressive and anxiety disorders and adherence Population-based health survey, Quebec, Canada 2811 community adults, ages 65 and older, final sample 926 subjects who took antihypertensive drugs for 2 years Adherence strongly associated with depression and anxiety disorders in men [130] Sexual activity and function in hypertensive pts (National Social Health, Life and Aging Project) Nationally representative sample of 3005 community-dwelling adults 37-85 years, classified by HT status: treated, untreated, and no HT ACEI, ARB, diuretic, CCB, b-blocker, and a-blocker No significant associations between antihypertensive medication class and sexual activity or problems in men and women Relationship between HT and sexual health did not differ between men and women [143] ED in high-risk HT pts receiving b-blockers ED assessed by the IIED 1007 pts, mean age 57.9 years…”
Section: Referencesmentioning
confidence: 99%
“…Dans une étude plus récente réalisée chez des sujets recevant pour la première fois un traitement anti-HTA, il a été mis en évidence une moins bonne observance chez les femmes [7]. L'observance au traitement anti-HTA serait significativement associée à la dépression et l'anxiété chez les hommes, mais pas chez les femmes [8].…”
Section: Introductionunclassified
“…Relatedly, given the small sample size, we were not statistically powered to explore whether gender moderates the association of anxiety sensitivity to medication non-adherence, though prior work has shown that depression and anxiety might have differential implications for medication adherence among men and women. 30 Third, we did not conduct comprehensive assessments of psychiatric disorders such as those generated from clinical interviews such as the CAPS for PTSD or the SCID, and thus cannot rule out whether the association of anxiety sensitivity with medication nonadherence is due to confounding from a psychiatric disorder. However, in models that adjusted for depression and PTSD symptoms, and in sensitivity analyses that further adjusted for state anxiety, we continued to see a robust association between anxiety sensitivity and medication nonadherence.…”
Section: Discussionmentioning
confidence: 99%